Evaluasi Premi Joint Life Pasangan Suami Istri Menggunakan Copula Frank - I Nyoman Widana; Ni Made Asih (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2018)
This paper introduces the joint life satatus for married couples with independent and dependent mortality models. Using Frank copula and Indonesia Life Tables 2011, we evaluate the impact of dependent future lifetimes on the net single and level premium. The results show premium rates are reduced if models of dependent future lifetime are used compared to the models using an assumption of independence.